Epistemologi Tafsir Jama>luddi>n Al-Qa>simi> Studi Tafsir Mah}a>sin al-Ta’wi>l. - Rofi’udin; Masruchin; M. Dani Habibi; Rofi’udin, Rofi’udin (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2025)
Abstract The phenomenon of Qur'anic exegesis studies continues to evolve according to the needs of the ummah for an authoritative and contextual understanding of the sacred text. One of the main issues is how to formulate an exegetical epistemology capable of connecting classical tradition with modern discourse. This article examines the epistemology of the tafsir Mahāsin al-Ta'wīl by Jamāluddīn al-Qāsimī, a productive scholar who compiled a complete 30-juz tafsir. This research aims to describe the uniqueness of al-Qāsimī's exegetical epistemology, including its sources, methodology, school, characteristics, approach, and validity, using library research and qualitative-descriptive analysis methods. The results show that al-Qāsimī's exegetical epistemology is based on the Qur'an, hadith, the opinions of the Companions, linguistic authority, and previous exegetes, using the bi al-ma'tsūr method accompanied by bi al-ra'y within a taḥlīlī framework. His tafsir exhibits characteristics of fiqh, scientific, theological, socio-cultural, and linguistic aspects, with validity evident in the consistent use of authoritative sources, as seen in QS. al-Baqarah: 223. This research affirms that al-Qāsimī's exegetical epistemology serves as a bridge between classical and modern tafsir traditions and opens opportunities for developing contemporary contextual tafsir methodologies. Keywords: Classical and modern tafsir; Jamaluddin Al-Qasimi; Mah}asin al-Ta’wil; Tafsir epistemology.